Home security system using Arduino / Ahmad Hazmi Lawrence - Lawrence, Ahmad Hazmi (2019)
A home with no security system is vulnerable to intruders such as robbery which will lead to loss of personal belongings. The home security system using Arduino can help to reduce the chances of undesirable loss of personal belongings. This system are applicable to houses and apartment room. This system can help to detect the presence of intruders and can alert the home owners by notifying them using GSM technology. Several sensors were used to detect the presence of intruders in this. The combinations of these sensors allow the system to capture the presence of intruders by 3 methods. Firstly, home security system using Arduino can detect intruders by motions inside the house or apartment room. Testing for this method have been done by moving objects in front of the sensor. Second method detects intruders inside the house is by tripping laser that have been set inside the house. This method was tested by blocking the reading of the laser beam to cover the emitted laser. Whenever intruders move across the laser beam, it will then trigger the alarm and notify the home owner. For the third method, vibration sensors was also implemented at the window to detect if any intruders try to break inside the house using the window. In this paper, the design and development of affordable home security system was presented.